The project-based learning model and its contribution to life skills in biology learning: A systematic literature network analysis - Ida Yayu Nurul Hizqiyah; Ikmanda Nugraha; C. Cartono; Yusuf Ibrahim; Ilah Nurlaelah; Meily Yanti; Siti Nuraeni (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
This review examines the potential of Project-Based Learning (PjBL) to enhance students' life skills in the field of biology, and analyzes the challenges that may hinder its implementation. Using a Systematic Literature Network Analysis (SLNA), which combines Bibliometrics Analysis (BA) and Systematic Literature Review (SLR), this study analyzed articles from SCOPUS that met specific criteria. The findings reveal that PjBL is associated with e-learning and blended learning, and that the majority of articles on PjBL were published in 2020, particularly in the Journal of Microbiology & Biology Education. Additionally, this SLNA highlights the contributions of these articles to the development of various life skills in biology learning. By identifying key trends and insights from existing literature, this study sheds light on the potential of PjBL to enhance students' biology education and their ability to apply it in their daily lives.